2020
DOI: 10.11609/jott.5479.12.8.15784-15793
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and synanthropy of flies (Diptera: Calyptratae) from Ecuador, with new records for the country

Abstract: The Calyptratae are one of the most diverse groups of Diptera.   Some species have immature states involved in the decomposition of organic matter of animal origin (i.e., they are sarcosaprophagous).  In this study, we examined the diversity and synanthropy of sarcosaprophagous calyptrates in several environmental zones of the Ecuadorian Andes.  Captures were performed in an urban zone located in the Tocachi community with monocultures (MC) and polycultures (PC), a rural zone with an agroecological farming sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Several species of Limnophora have been evaluated, in Argentina for example, through the synantrophy index, giving as a result that 100% of the collected individuals were found in rural zones (Patitucci 2010). While in Ecuador research conducted by Blacio et al (2020), revealed that Limnophora marginata Stein, 1904 shows a preference for urban areas, with a high index of synantrophy. In addition, the species is distributed in Argentina, Brazil, Colombia, and Ecuador (Fogaça and de Carvalho 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several species of Limnophora have been evaluated, in Argentina for example, through the synantrophy index, giving as a result that 100% of the collected individuals were found in rural zones (Patitucci 2010). While in Ecuador research conducted by Blacio et al (2020), revealed that Limnophora marginata Stein, 1904 shows a preference for urban areas, with a high index of synantrophy. In addition, the species is distributed in Argentina, Brazil, Colombia, and Ecuador (Fogaça and de Carvalho 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sarconesia chlorogaster (Wiedemann, 1830) blowfly is known as one of the most important species in the forensic insect fauna (Moura et al, 1997;Mulieri et al, 2006;Mariluis et al, 2008;Battán-Horenstein et al, 2016, Castillo et al, 2017. The bionomy of this species has been studied in Brazil (Queiroz et al, 1985), and about synantropy and diversity of Calliphoridae (Blacio et al, 2020).…”
mentioning
confidence: 99%